Association between socioeconomic status, type 2 diabetes and its chronic complications in Argentina - Elgart, Jorge Federico (2014)
Aim: To compare the socioeconomic status (SES) of people with type 2 diabetes (T2DM) in Argentina (Co´ rdoba) with and without major chronic complications of diabetes, with that recorded in persons without diabetes matched by age and gender. Methods: For this descriptive and analytic case–control study, potential candidates were identified from the electronic records of one institution of the Social Security System of the city of Co´ rdoba. We identified and recruited 387 persons each with T2DM with or without chronic complications and 774 gender- and age-matched persons without T2DM (recruitment rate, 83%). Data were obtained by telephone interviews and supplemented with data from the institution’s records. Group comparisons were performed with parametric or nonparametric tests as appropriate. We used ordinary least squares to regress household income and the difference between income and household expenses on diabetes status, age, sex, education and body mass index. Results: Persons with T2DM, particularly those with complications, reported fewer years of general education (13.6 4.2 years vs. 12.2 4.4 years), a lower percentage of full time jobs (43.0% vs. 26.9%), lower salaries and monthly household income among those with full-time jobs (> 5000 ARG$: 52.6% vs. 24.5%), and a higher propensity to spend more money than they earned (expenditure/income ratio 1: 10.2% vs. 16.0%). The percentage of unmarried people was also higher among people with type 2 diabetes (7.0% vs. 10.9%). Conclusion: T2DM and the development of its complications are each positively associated with lower SES and greater economic distress in Argentina.